Multiple Tubercular Brain Abscesses with Obstructive Hydrocephalus in an Immunocompetent Child: A Case Report - Sahoo, Ipsita K (J Pediatr Neurosci, 2020)
Tubercular brain abscesses are rare manifestations in children, and very few cases have been reported till date. It is characterized by an encapsulated collection of pus, containing viable tubercular bacilli. Antitubercular treatment (ATT) is the mainstay of treatment along with surgical drainage or aspiration or excision of the abscess. We hereby report a case of a 15-month-old child with multiple tubercular brain abscesses with obstructive hydrocephalus, managed with ATT and ventriculoperitoneal shunt.